Effects of Regular and Continuous Exercise on Oxidative Stress and Apoptosis - Çakar, Fatih; Yüce, Abdurrauf; Arkalı, Gözde (My University, 2022)
In this study, it was aimed to investigate the effects of intense acute exercise and regular and continuous exercise on oxidative stress parameters and apoptosis-related Bax and Bcl-2 protein levels in rats. In the study, 1 control and 4 experimental groups were formed from 35 male Wistar-Albino rats, 7 in each group. The control group was not exercised, the other four groups exercised at a speed of 1.5 km/h for 1 hour on a 20 degree incline treadmill every day. Control and 1st group at the end of the 1st day, 2nd group 7th day, 3rd group 15th day and 4th group 30th day were sacrificed under anesthesia. Malondialdehyde (MDA) as an indicator of lipid peroxidation, and Glutathione (GSH), Catalase (CAT), Glutathione Peroxidase (GSH-Px) levels as an antioxidant indicator in muscle and plasma levels were measured. Bax and Bcl-2 protein expression levels were also checked for apoptosis in skeletal muscle. According to the results obtained, skeletal muscle and plasma MDA values increased after acute exercise (P<0.05), while skeletal muscle and plasma GSH-Px, CAT values increased significantly after continuing regular and continuous exercise (P<0.01). It was observed that Bax protein expression level increased, Bcl-2 protein expression level decreased and Bax/Bcl-2 ratio increased in acute exercise (p<0.05). As a result, it was concluded that regular and continuous exercise has a protective effect against oxidative stress and apoptosis triggered by acute exercise can be suppressed by regular and continuous exercise.
Keywords: Exercise; Apoptosis; Bax/Bcl-2; Oksidative stress